An Uncommon Case of Solitary Peripheral Osteoma in the Mandible. (14th December 2015) - Agrawal, Rohit; Agrawal, Shipra; Bhargava, Shitij; Motlani, Mahesh; Agrawal, Rahul
Abstract : Osteoma is a benign osteogenic lesion which is composed of well differentiated mature compact and/or cancellous bone that proliferates continuously. Its prevalence is 4%. Its pathogenesis is still controversial. Solitary peripheral osteoma of craniofacial region is a rare finding. We report a case of 30-year-old female having solitary peripheral osteoma present on the lingual cortex of the left posterior mandible which was initially asymptomatic but now is causing discomfort while chewing and not associated with Gardner's syndrome. We also laid emphasis on its clinical, differential diagnosis, radiological, surgical, and histopathological features. The aim of this paper is to present an uncommon case of solitary peripheral osteoma in the mandible along with analysis of literature for peripheral osteomas of jaws and to contribute to the knowledge concerning the pathogenesis, differential diagnosis, and management of these lesions.